2020
DOI: 10.1186/s12889-019-7892-9
|View full text |Cite
|
Sign up to set email alerts
|

Requiring smartphone ownership for mHealth interventions: who could be left out?

Abstract: Background Mobile health (mHealth) interventions have the potential to improve health through patient education and provider engagement while increasing efficiency and lowering costs. This raises the question of whether disparities in access to mobile technology could accentuate disparities in mHealth mediated care. This study addresses whether programs planning to implement mHealth interventions risk creating or perpetuating health disparities based on inequalities in smartphone ownership. Methods Video Dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 19 publications
1
32
0
2
Order By: Relevance
“…Similarly, we observed an increasing trend in disinterest with decreasing levels of education. Prior research demonstrates that adults with lower incomes and lower levels of education display a significantly reduced odds of using digital health services and owning mobile devices [ 22 , 23 ], and as such, may be less comfortable with using devices for mobile health (mHealth) purposes. Indeed, our findings demonstrate that non-owners of mobile devices report a significantly higher lack of interest or willingness to digitally share medical images with HCPs.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, we observed an increasing trend in disinterest with decreasing levels of education. Prior research demonstrates that adults with lower incomes and lower levels of education display a significantly reduced odds of using digital health services and owning mobile devices [ 22 , 23 ], and as such, may be less comfortable with using devices for mobile health (mHealth) purposes. Indeed, our findings demonstrate that non-owners of mobile devices report a significantly higher lack of interest or willingness to digitally share medical images with HCPs.…”
Section: Discussionmentioning
confidence: 99%
“…A US nonnephrology study exploring mobile health readiness in older individuals receiving health care reported high levels of access to mobile health devices and the internet, with 60% of respondents using mobile devices and the internet for health information (21). In those with chronic health conditions, device ownership is high (22,23) and attitudes are positive (24), with a willingness to replace face-to-face physician visits with mobile health (25).…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, then, our study demonstrates that equitable access to mHealth app-based interventions among older adults in rural KwaZulu-Natal may require provision of smartphones and internet access to avoid perpetuating health disparities. 22 Distinct from national South African statistics, women in our rural setting were more likely than men to own cell phones and smartphones. This was surprising and perhaps hints at changing societal and cultural norms for the surveyed female population.…”
Section: Discussionmentioning
confidence: 78%